Dual Agent Distortions in Real Estate Transactions. (29th March 2015) - Johnson, Ken H.; Lin, Zhenguo; Xie, Jia
<x xml:space="preserve">Abstract</x> This article investigates price distortions in dual agent real estate transactions. Consistent with the literature, we find that, on average, dual agent has a null effect on sale price. However, dual agent distortions on sale price emerge after controlling for the ownership of the property. Dual agent is associated with a 6.35% price premium on agent‐owned properties, but a 25.10% price discount on government‐owned properties and a 5.14% discount on bank‐owned properties. In addition, market conditions also play an important role in such price distortions.